PRE-SERVICE ENGLISH TEACHER PERCEPTION ABOUT HIGHER ORDER THINKING SKILLS (HOTS) IN THE 21ST CENTURY LEARNING - Desy Nur Fakhomah; Melati Sri Utami (Sanata Dharma University Yogyakarta, 2019)
In Indonesia, the consciousness of the significance of HOTs becomes an educational purpose. This study aims to investigate what teachers perception and the difficulty in implementing HOTS in 21st century of English language teaching. This research adopted a sequential explanatory mixed methods design (Creswell, 2014). It is regarded as explanatory because the initial quantitative data results are explained with the qualitative data. There were 5 participants in total who have volunteered for this study. They are the Pre-service English Teacher of Professional Teacher Program from different universities using randomized sampling. This study indicated that the participants have a high perception in implementing HOTs in the classroom. However, the participants face some difficulties in its implementation, such as time management and students ability.DOI: doi.org/10.24071/ijiet.2019.030104